Greco-Egyptian interactions: literature, translation, and culture, 500 BCE-300 CE - Rutherford, Ian (Oxford University Press, 2016)
Contact and interaction between Greek and Egyptian culture can be traced in different forms over more than a millennium: from the sixth century BC, when Greeks visited Egypt for the sake of tourism or trade, through to the Hellenistic period, when Egypt was ruled by the Macedonian-Greek Ptolemaic dynasty who encouraged a mixed Greek and Egyptian culture, and even more intensely in the Roman Empire, when Egypt came to be increasingly seen as a place of wonder and a source of magic and mystery. This volume addresses the historical interaction between the ancient Greek and Egyptian civilizations in these periods, focusing in particular on literature and textual culture. Comprising fourteen chapters written by experts in the field, each contribution examines such cultural interaction in some form, whether influence between the two cultures, or the emergence of bicultural and mixed phenomena within Egypt. A number of the chapters draw on newly discovered Egyptian texts, such as the Book of Thoth and the Book of the Temple, and among the wide range of topics covered are religion (such as prophecy, hymns, and magic), philosophy, historiography, romance, and translation - Publisher
Literaturangaben. - Index
"Many of the papers in this volume had their origin in a conference at the University of Reading, Graeco-Aegyptiaca/Aegypto-Graeca: Interactions between Greece and Egypt 700 BCE-300 CE." - (Acknowledgements)
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Egypt -- Relations -- Greece; Greece -- Relations -- Egypt; Egypt -- Civilization -- Greek influences; Greece -- Civilization -- Egyptian influences; Greece -- Intellectual life; Egypt -- Intellectual life; Konferenzschrift -- 17.09.2007-19.09.2007 -- Reading; Geschichte 500 v. Chr.-300; Kultur; Übersetzung; Literatur; Ägypten; Griechenland